The Menace of Forced Marriage on the Educational Development of Female Muslim Youths in Ghana: The Case of Akim Oda - Kuyateh, Mustapha Abdullah (Borneo International Journal of Islamic Studies, 2023)
Although Islam allows the parents to make arrangements for their children, especially for marriage, it never stipulated laws ignoring their consent. This is, however, the case in Akim Oda, where women are forced into marriages in the name of Islam without their consent. The situation is worrying, and women, especially female Muslim youths who are forced into marriages, continue to be disadvantaged in terms of education and training. This research work, therefore, investigates the reasons for such happenings and compares it with Islam’s view on marriage within the context of forced marriage as practiced in Akim Oda. In this regard, the qualitative research method was employed. The primary data collection method included interviews with fifteen (15) respondents, including Chiefs, Imams, religious leaders, opinion leaders, parents, and female Muslim youths. Findings from the field indicate that forced marriages, in most cases within the study area, were to the benefit of the family and not to the female Muslim youths. It was also observed from the findings that parents and relatives collect monies for their daughters who ended up dropping out of school for marriages they are unprepared for.